FORMATION AND HPLC ANALYSIS OF THE NATURAL LAKE PIGMENT OBTAINED FROM MADDER (RUBIA TINCTORUM L.) - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2010)
In this work, madder lake pigments, aluminium-madder, tin-madder and iron-madder, were obtained by the reaction of KAI(SO(4))(2)center dot 12H(2)O, FeSO(4)center dot 7H(2)O and SnC12 center dot 2H(2)O solutions with madder. High performance liquid chromatography (HPLC) with diode-array detection (DAD) method was utilized for the identification of the lake pigments. Reversed-phase HPLC with diode-array UV-V is spectrophotometric detection was used in this identification. The extraction of dyestuffs from the lake pigments was carried out with HCI / methanol / water (2:1:1; v/v/v) solution. From the results of the HPLC analysis of the madder lake pigments, it was determined that the alizarin present in the lake pigments was precipitated by A1(III), Fe(II) and Sn(II).
Keywords: Madder; dyestuff; pigment; alizarin; anthraquinone; HPLC; PERFORMANCE LIQUID-CHROMATOGRAPHY; ANTHRAQUINONES; COLOR